2005
DOI: 10.1080/02841850510021210
|View full text |Cite
|
Sign up to set email alerts
|

Primary extracranial meningioma of the sinonasal tract

Abstract: Meningiomas occurring outside the cerebrospinal axis can be primary at an extracranial site (nasal cavity, paranasal sinuses, and nasopharynx) or secondary extending from an intracranial lesion. Magnetic resonance imaging findings of an 8-year-old child with primary meningioma before and after surgery have been reviewed and compared to computed tomography and histological evaluation. The child had difficulty breathing through the left nostril and tearing of the left eye. After physical and radiological examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…While surgery is the treatment of choice, there are a number of challenges due to the invasiveness of the tumors and the complexity of the anatomy within the sinonasal tract and ear and temporal bone, although scalp and soft tissues lesions are no less difficult to remove if they are adjacent to vital structures. It may be necessary to utilize a multidisciplinary approach with a combination of intracranial, temporal bone, maxillofacial, and skull base techniques to achieve total resection, possibly including widely exenterative procedures to achieve this end [10, 16, 29, 31, 37, 54–61]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While surgery is the treatment of choice, there are a number of challenges due to the invasiveness of the tumors and the complexity of the anatomy within the sinonasal tract and ear and temporal bone, although scalp and soft tissues lesions are no less difficult to remove if they are adjacent to vital structures. It may be necessary to utilize a multidisciplinary approach with a combination of intracranial, temporal bone, maxillofacial, and skull base techniques to achieve total resection, possibly including widely exenterative procedures to achieve this end [10, 16, 29, 31, 37, 54–61]. …”
Section: Discussionmentioning
confidence: 99%
“…The histopathologic diagnosis is usually straightforward; however, the diagnosis may pose challenges in these unexpected locations where the differential diagnosis includes paraganglioma, carcinoma, melanoma, schwannoma, and olfactory neuroblastoma, among others. Previous reports on meningioma in uncommon locations are largely limited to individual cases or small series [2, 4–10, 1216]. The objective of this retrospective study is to present our experience, the largest series to date, with extracranial meningiomas, highlighting clinicopathologic features and outcome associated with the surgical treatment of these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic presentations are among the most rare with Teague et al reporting a metastatic meningioma within the lungs 5. There are only a handful of reported primary ectopic extracranial meningiomas in the literature with such examples including primary ectopic meningioma of the nose6 and ethmoid sinus 7…”
Section: Discussionmentioning
confidence: 99%
“…Among cases involving the sinonasal tract, Thompson et al described that most of the tumors were found to affect more than one sinus or a combination of nasal cavity and paranasal sinuses and the most commonly affected sinus was the frontal sinus (16). A sinonasal meningioma originating from the sphenoid sinus is relatively rare, whereas there are some isolated case reports of sinonasal meningioma mainly involving the ethmoid sinus (1,8,11,13).…”
Section: Discussionmentioning
confidence: 99%